Perfection of the special preparation of volleyball players - Volodymyr Bogush; Sergiy Getmantsev; Olga Sokol; Oksana Reznichenko (Kharkiv State Academy of Physical Culture, 2015)
Purpose: to develop and apply the complex of exercises for perfection of the special physical preparation of volleyball players and its constituents: special quickness, force, endurance. Material and Methods: sportsmen (candidates in sport masters, I and II digits) inspected in age from 16 to 23 in an amount 40 persons; the special quickness and its constituents are probed: latent period of the reaction, the speed of individual movements; maximum force in various modes; endurance - speed, hopping, power. Results: at drawing on the offered complex of exercises the improvement of indexes of speed and endurance hopping, speed-power capabilities is marked at stimulation of tension of muscles in the conditions of development of a maximum of dynamic effort. Conclusions: terms and methods are certain for the effective conducting of training process, which provides optimum intercommunication of levels of bodily and functional conditions, technical and tactical preparation.